A genetic network mediating the control of bud break in hybrid aspen. Issue 1 (December 2018) - Singh, Rajesh; Maurya, Jay; Azeez, Abdul; Miskolczi, Pal; Tylewicz, Szymon; Stojkovič, Katja; Delhomme, Nicolas; Busov, Victor; Bhalerao, Rishikesh
Abstract In boreal and temperate ecosystems, temperature signal regulates the reactivation of growth (bud break) in perennials in the spring. Molecular basis of temperature-mediated control of bud break is poorly understood. Here we identify a genetic network mediating the control of bud break in hybrid aspen. The key components of this network are transcription factorSHORT VEGETATIVE PHASE-LIKE (SVL), closely related to Arabidopsis floral repressorSHORT VEGETATIVE PHASE, and its downstream targetTCP18, a tree homolog of a branching regulator in Arabidopsis.SVL andTCP18 are downregulated by low temperature. Genetic evidence demonstrates their role as negative regulators of bud break.SVL mediates bud break by antagonistically acting on gibberellic acid (GA) and abscisic acid (ABA) pathways, which function as positive and negative regulators of bud break, respectively. Thus, our results reveal the mechanistic basis for temperature-cued seasonal control of a key phenological event in perennial plants. Molecular mechanism of how temperature-mediated control of bud break in perennial plants remains unclear. Here, the author show that transcriptional factorSHORT VEGETATIVE PHASE-LIKE and its downstream targetTCP18 are negative regulators of hybrid aspen bud break.